Randomized controlled trial for evaluation of efficacy and pain during photodynamic therapy for actinic keratosis of face and scalp comparing two irradiation protocols - ER, Oliveira; AG, Salvio; HA, Miot [UNESP]; MB, Requena [UNESP]; MMC, Medeiros; MR, Garcia; LPF, Abbade [UNESP] (Elsevier, 2022)
Background: Pain is a frequent adverse event during photodynamic therapy, which can limit treatment acceptance. This study aimed to evaluate the efficacy and pain during photodynamic therapy with two irradiation protocols in patients with actinic keratosis on the face and scalp. Methods: In this intra-patient randomized controlled trial, participants were randomly allocated to receive photodynamic therapy with methyl aminolevulinate and red light on the right or left side with protocol 1 (irradiation device in contact with the skin) and protocol 2 (device 3 cm away from the skin). There was a 15-day interval between the protocols. The primary outcome was the frequency of mean intensity of moderate or severe pain during photodynamic therapy. Secondary outcomes were actinic keratosis clearance rate, protoporphyrin IX consumption, participant preference, skin appearance, and adverse events. Results: Forty-one participants were included, yielding 47 and 50 randomized sites for protocols 1 and 2. There was no difference in the frequency of moderate and severe pain, with a relative risk of 1.09 (95% CI 0.70–1.70), p>0.05. An actinic keratosis count reduction >60% was observed in both protocols (p<0.01), with no difference between them. There was no difference in protoporphyrin IX consumption. Most treated sites were of good to excellent quality. There was a greater patient preference for protocol 2 (p<0.01). Conclusions: The pain intensity was similar between the protocols, and the protocols were equally effective for actinic keratosis clearance, protoporphyrin IX consumption, and improvement in the quality of the treated areas. Both protocols may be considered safe.
Keywords: Keratosis actinic; Pain; Photochemotherapy; Photodynamic Therapy; Randomized controlled trial